Kommentar zu den 2013 Leitlinien der Europäischen Gesellschaft für Kardiologie (ESC) zum Management der stabilen koronaren Herzkrankheit (KHK) - Sechtem, U.; Achenbach, Susanne; Gitt, A. K.; Marx, N.; Kelm, M.; Schächinger, V. (Der Kardiologe, 2015)
The 2013 guidelines of the European Society of Cardiology (ESC) on the management of stable coronary artery disease (CAD) give practical recommendations for the use of diagnostic tools to identify hemodynamically relevant coronary artery stenoses. Furthermore, they give advice for the management of previously symptomatic patients with known obstructive or non-obstructive CAD, who have become asymptomatic with treatment and need regular follow-up. The selection of appropriate diagnostic tests is based on the tabulated pretest probability of the patient, which plays a central role in the diagnostic algorithm. An invasive approach is recommended only for patients who either have severe angina or who are judged to be at high risk for adverse events based on clinical evidence or the results of diagnostic tests. The optimal use of preventive and antianginal medications is shown in a scheme which includes the new antianginal drugs. The guidelines recommend a percutaneous coronary intervention (PCI) as an alternative to bypass surgery in patients with multivessel disease or left main stem stenosis if the SYNTAX score is low.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Diagnostics; Follow-up; Indications; Recommendation; Therapy